Training Evaluation Management Model of CT and MRI Quality Control Based on The ACR Phantom Using View Dex Administrator - Gatot Murti Wibowo; Fahkruddin Fahkruddin; Rustono Rustono; Muhammad Khafid (Universitas Negeri Semarang, 2022)
Background: CT and MRI QC Training must have the three stages to perform, namely planning, implementation, and evaluation. In the evaluation stage, the content being tested was not comprehensive, and was still in the form of a paper base test. The study aims to develop computer-based test that is integrated with ViewDex application. Methods: The waterfall models is employed in the research development. In the process of developing a paper base of test-based evaluation system developed into a computer base test. The development of administrator ViewDex software (Java 2 platform, version 2.0) includes the stages: identification, system design, validation, program development, implementation, validation, function testing, performance testing, and maintenance stages. Limited evaluation about function and performance of the developed applications is carried out through the tests. Results: The developed ViewDex administrator can be used for evaluating the participants who joint the training program on QC CT and MRI. The performance of the ViewDex administrator application as a whole in the category is very feasible to employ as a model for evaluating the QC training program on CT and MRI. Conclusion: The ViewDex administrator application performs the process of exporting the participant data, creating questions, and importing the test results quickly and easily. The application runs successful to evaluate participants' knowledge about CT and MRI image quality performances after completing the training course entirety. All items of buttons available on the ViewDex administrator can function properly. The menu for testing users is in a good design, showing final evaluation results.